2013
DOI: 10.1075/jlac.1.1.05mat
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cross-cultural pragmatic taxonomy of insults

Abstract: The aim of this paper is to explain the use of insults from a relevance-theoretic perspective. To that end, our analysis takes into consideration four variables that, we believe, play a major role in how insults are produced an interpreted: (a) the conventional or innovative nature of the insult; (b) the underlying intentionality (to offend, to praise or to establish/maintain social bonding; (c) the in/correct interpretation of the insult, and (d) the addressee's reaction or lack thereof. The combination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 13 publications
1
17
0
4
Order By: Relevance
“…However, Culpeper (2011) presents an insult as one category of the Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/4/15 7:44 AM impoliteness formulae. An insult may be understood as a distinct type of speech activity encompassing remarks which invoke negative characteristics of the target, so far studied primarily in sociolinguistics (Labov 1972;Illie 2001;Evaldsson 2005;Stokoe and Edwards 2007) but more recently also in pragmatics (Mateo and Yus 2013), which is still in need of investigation in terms of impoliteness. Mateo and Yus (2013) propose that insults can perform three functions: offence, praise and social bonding.…”
Section: Notions Related To Impolitenessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Culpeper (2011) presents an insult as one category of the Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/4/15 7:44 AM impoliteness formulae. An insult may be understood as a distinct type of speech activity encompassing remarks which invoke negative characteristics of the target, so far studied primarily in sociolinguistics (Labov 1972;Illie 2001;Evaldsson 2005;Stokoe and Edwards 2007) but more recently also in pragmatics (Mateo and Yus 2013), which is still in need of investigation in terms of impoliteness. Mateo and Yus (2013) propose that insults can perform three functions: offence, praise and social bonding.…”
Section: Notions Related To Impolitenessmentioning
confidence: 99%
“…An insult may be understood as a distinct type of speech activity encompassing remarks which invoke negative characteristics of the target, so far studied primarily in sociolinguistics (Labov 1972;Illie 2001;Evaldsson 2005;Stokoe and Edwards 2007) but more recently also in pragmatics (Mateo and Yus 2013), which is still in need of investigation in terms of impoliteness. Mateo and Yus (2013) propose that insults can perform three functions: offence, praise and social bonding. It might be observed that whilst the first one is orientated towards impoliteness, the latter two appear to serve solidarity politeness.…”
Section: Notions Related To Impolitenessmentioning
confidence: 99%
“…Hence, we cannot equal verbal aggression and insults across the board. Surprisingly, there is not much genuine speech-act theoretical work on insults, so I stick to the recent works of Neu (2008), Culpeper (2011), and Mateo and Yus (2013). 15 The force of insults becomes crystal-clear when offensive words or constructions are considered.…”
Section: Bald-faced Lies Are Acts Of Verbal Aggressionmentioning
confidence: 99%
“…While the promising approach of Mateo and Yus (2013) combines the relevant pragmatic parameters, a definition of insulting in speech-act theoretical terms is missing. To be in line with speech-act definitions pursued in this paper, I propose the following felicity conditions for insulting: 16 (22) Insulting Propositional content rule What is to be expressed is any proposition p or expressive meaning e functional for insulting.…”
Section: Bald-faced Lies Are Acts Of Verbal Aggressionmentioning
confidence: 99%
See 1 more Smart Citation